AI ASSISTED FACIAL RECONSTRUCTION OF PANJI’S LOVER CHARACTER IN PENATARAN TEMPLE’S BAS RELIEFS USING SKETCH TO IMAGE METHOD - Andito, Tegar (Yayasan Sinergi Widya Nusantara, 2024)
Purpose: Purpose of this research is to realistically reconstruct face of Panji’s Lover character at 51st panel of Teras Pendopo structure’s bas relief in Penataran Temple complex as guide for concept art creation of Panji’s Lover character. Research methods: This experiment consists of two steps. First is manually drawing a sketch of the character and describing her facial features. The second step is image generation by artificial intellegence employing sketch-to-image method using created sketch as base image and the description as prompt. The used artificial intelligence (AI) program is Stable Diffusion 1.5 with ControlNet add on. The used AI models are Realistic Vision 5.1 and Dreamshaper 8. Findings: Images generated with Realistic Vision 5.1 model are closest to sketch and description of original bas relief. Implications: The results of this experiment can’t be used as final artwork but can be guide for concept art creation for both Candra Kirana and Galuh Ajeng character in any future visual art projects based on Panji Tales stories.